Synthesis of BF3 catalyzed Mannich derivatives with excellent ee from phenylpropanolamine, study of their antimicrobial activity and molecular docking. Issue 19 (1st October 2015) - Chennakesava Rao, K.; Easwaramoorthi, K.; Arun, Y.; Balachandran, C.; Muralidhara Rao, K.S.; Govindhan, M.; Emi, Nobuhiko; Prakasam, T.; Perumal, P.T.
Graphical abstract: Potential antimicrobial activities found in4b, 4c, 4d, 4e, 5a and5e than standard streptomycin and ketoconazole. Abstract: Antimicrobial agents4a –g and5a –g with very good potency were synthesized with 100% ee from phenylpropanolamine (norephedrine) by BF3 catalyzed three components one pot Mannich reaction in good yields. Obtained compounds were characterized using spectral techniques. Antimicrobial study of these compounds revealed a good to very high potential activity against tested microbes when compared to standard antimicrobial drugs streptomycin and ketoconazole. These synthesized compounds exhibited significant minimum inhibitory concentration (MIC) values against Gram positive and Gram negative bacteria. Amongst compound4b, 4c, 4d, 4e, 5a, and5e exhibited very high potent MIC values against tested twelve bacteria and three fungi when compared to control. When subjected to molecular docking, in silico studies revealed significant binding energies ranging from −7.06 to −8.90 kcal/mol for all obtained compounds towards target receptor DNA topoisomerase IV and amongst compounds4b and4d have shown maximum binding energies 8.70 and 8.90 kcal/mol, respectively.